Past and future evolution of nighttime urban cooling by suburban cold air drainage in Aachen - Sachsen, Timo; Ketzler, Gunnar; Knörchen, Achim; Schneider, Christoph (DIE ERDE – Journal of the Geographical Society of Berlin, 2014)
In urban areas situated downstream of rural areas, cold air drainage flow contributes to reduced nighttime temperatures and reduced pollutant concentrations. In this study, the impact of historical, present and possible future land-use changes upon evening cooling by suburban cold air drainage flow is analysed by using the numerical cold air drainage model KLAM_21 of the German Weather Service (DWD). In order to do this, land-use patterns of the year 1810 and 1910 are reconstructed. Furthermore, potential land-use scenarios are developed, considering both a scenario with beneficial cold air drainage characteristics and a second adverse scenario. Past, present and future land-use data are used as model input. To validate model results in the present land-use situation, empirical data from field measurements are used to compare modelled and effective cold air drainage flow characteristics. Model data for 14 reference areas – including suburban and inner city sites – are compared with regard to the cooling rate 3 h after sunset. The results show distinctive effects of accumulated long-term urban land-use changes on the suburban cold air drainage flow. In the city centre, for example, the modelled mean cooling rate decreases from 3.6 K in 1810 to 2.8 K in 1910 and to 2.4 K in 2010. In contrast to this, appropriate measures to stop or even reverse the trend of decreasing cooling rates are shown. Intensified urban cooling by nocturnal cold air drainage can contribute to mitigating probable future global warming effects.